Alterations of growth hormone levels during a swimming training period as they are affected by sex - Avlonitou, E.; Botoula, E.; Thalassinos, N.; Pavlou, K. N. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
This study attempted to examine the training adaptations of hGH at rest, and how this process is affected by sex. Summary: These data suggest that regular aerobic exercise affects resting GH levels by enhancing them in both sexes. Subsequently, there was a gender difference upon GH response, which was independent of the influence of exercise training, with the females showing a more pronounced serum GH concentration at rest, either with training or without training, as compared to their age and fitness matched male counterparts.